The Meaning Analysis of Slang Words in Instagram Used By K-Popers - Linta Wafdan Hidayah; Nora Fitriyah; Muhammad Safdar Bhatti (Wacana Didaktika, 2022)
Language has a lithe and dynamical nature that will make new possibilities in communications, so that it is not possible for language to stop at one word and one meaning only Because language changes as rapidly as human life grows. Language is divided into two parts, that is, standard English and non-standard English. There are different kinds of non-standard languages, Slang is one of them. This research employed a qualitative method, this research discusses constructivism, which requires an understanding of the theory of phenomena used, and objective data.The data taken for this research is collected from the lnstagram K-popers account. From those references, then the researcher collected the slang words and phrases by underlining the important data which found awkard and difficult to be understood.This research employed a qualitative method, this research discusses constructivism, which requires an understanding of the theory of phenomena used, and objective data.From these references, researchers then collected slang words and sentences by providing a bottom line, important data that found unclear and difficult to understand. All data will be explained in detail on the description data from this research paper. Keywords: Instagram, K-popers, Slang. Abstrak: Bahasa memiliki sifat yang luwes dan dinamis yang akan membuka kemungkinan-kemungkinan baru dalam berkomunikasi, sehingga tidak mungkin bahasa berhenti pada satu kata dan satu makna saja. Bahasa dibagi menjadi dua bagian, yaitu bahasa Inggris standar dan bahasa Inggris non-standar. Ada berbagai jenis bahasa non-standar, Slang adalah salah satunya. Penelitian ini menggunakan metode kualitatif, penelitian ini membahas konstruktivisme, yang membutuhkan pemahaman tentang teori fenomena yang digunakan, dan data yang objektif. Data yang diambil untuk penelitian ini dikumpulkan dari akun Instagram K-popers. Dari referensi tersebut, kemudian peneliti mengumpulkan kata-kata dan frase slang dengan menggarisbawahi data-data penting yang dirasa janggal dan sulit dipahami. dan data objektif. Dari referensi tersebut, peneliti kemudian mengumpulkan kata-kata dan kalimat gaul dengan memberikan garis bawah, data penting yang ditemukan tidak jelas dan sulit dipahami. Semua data akan dijelaskan secara rinci pada deskripsi data dari makalah penelitian ini.